Pro SQL Server 2005 Reporting Services - Voytek, Walter; Landrum, Rodney; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2006)
SQL Server Reporting Services (SSRS) 2005 is the latest version of the reporting technology from Microsoft. This book examines all of the technology that SSRS provides to design, author, render and deploy professional business reports to the Web or to the company intranet (in a variety of formats, from HTML to XML, PDF, or TIFF), with detailed examples at every step. It covers all of the new functionality present in the 2005 version, including the new management and business intelligence development studios, as well as the new report viewer controls and end-user reporting tools. It also contains significantly expanded chapters on business intelligence, along with a wealth of tips and workarounds for effective development with SSRS. The authors are both highly experienced with SQL Server and with business reporting in the medical industry, which is subject to rigorous HIPAA regulations and strict security. It is not their intention to evangelize the product or present "idealized" examples based on the simple built-in schemas. Instead, they take a hard, critical look at the technology and provide exactly what the reader needs to know to deliver effective reports. Their code examples are based on real, complex schemas and the need to deliver versatile, dynamic reports, as well as on strict security and performance requirements. In summary, this book will provide you with step-by-step guides, best practices, and real code examples covering all of the common Reporting Services tasks, including: A detailed overview of the reporting architecture and tools The new Report Definition Language Standard, which is XML-based and allows you to define reports in VS.NET Building effective queries for high-performance reporting Building custom .NET applications with SSRS Rendering reports to HTML, XML, PDF and Excel Deploying secure reports, using Windows authentication through Active directory Business Intelligence reporting using SQL Server Analysis Services.
Introducing the Reporting Services Architecture -- Report Authoring: Designing Efficient Queries -- Using Report Designer -- Building Reports -- Using Custom .NET Code with Reports -- Rendering Reports from .NET Applications -- Deploying Reports -- Managing Reports -- Securing Reports -- Delivering Business Intelligence with SSRS -- Performing Ad Hoc Reporting Using Report Builder.
Keywords: Database management; Software engineering; Database Management; Software Engineering/Programming and Operating Systems